Main factors for the export of organic cocoa produced in the province of Marañon - Huánuco - Ramirez Arroyo, Rafael (2020)
This research aims to determine what are the key factors and how they in_uence the export of organic cocoa in the province of Marañón - Huánuco. For this purpose, the following key factors were proposed in the working hypothesis: production,  associativity, _nancing, technology, logistics, marketing and international prices. A descriptive design was developed, initially addressing each of the aforementioned factors, obtaining as a result that logistics has a high impact due to the poor road infrastructure in the area, associativity is constituted as a primary strategy to reach the desired exportable supply, The financing becomes an ally for cooperatives and / or associations allowing to face export costs and, finally, marketing strategies through participation in international fairs allow promoting the brand and generate new customers. In conclusion, logistics, associativity, financing, marketing strategies and production directly in-fluence the export of organic cocoa, while technology and the volatility of international prices do not have a very significant impact on the export process.